2021
DOI: 10.1039/d1sc03963f
|View full text |Cite
|
Sign up to set email alerts
|

Solvothermal depolymerization and recrystallization of imine-linked two-dimensional covalent organic frameworks

Abstract: Conditions for which imine-linked 2D COF polymerizations are temperature-sensitive are identified that enable a dissolution/repolymerization process akin to molecular recrystallization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Based on SEM images of drop-cast aliquots of the TAPB-DMPDA COF polymerizations isolated at different reaction times, the crystals reached their final sizes within 6 min (Figure S19A). We hypothesized that increasing the reaction temperature would slow nucleation based on our recent study of COF recrystallization 53 and the temperaturedependence of the imine/aldehyde equilibrium. Indeed, a polymerization temperature of 150 °C produced TAPB-DMPDA COF crystals of up to 20 μm in size.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on SEM images of drop-cast aliquots of the TAPB-DMPDA COF polymerizations isolated at different reaction times, the crystals reached their final sizes within 6 min (Figure S19A). We hypothesized that increasing the reaction temperature would slow nucleation based on our recent study of COF recrystallization 53 and the temperaturedependence of the imine/aldehyde equilibrium. Indeed, a polymerization temperature of 150 °C produced TAPB-DMPDA COF crystals of up to 20 μm in size.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Early mechanistic studies of imine-based 2D polymerizations suggested that the rapid formation of a polymer network followed by crystallization by imine exchange reactions occurred under most solvothermal conditions . More recently, imine-linked COF formation was found to be rapid , and, in some cases, thermally reversible, and two examples of micron-size and larger imine-linked 2D COF single crystals have been reported. , Wei and coworkers reported millimeter-sized crystals of an imine-linked 2D COF, TAPPy-PDA , using supercritical CO 2 as the reaction solvent and reaction times as short as 5 min, although the crystallinity was characterized by transmission electron microscopy (TEM) analysis rather than bulk X-ray diffraction . This 2D polymer had been reported previously as a polycrystalline powder by Bein and coworkers under traditional solvothermal conditions and reaction times of 1–3 days .…”
Section: Introductionmentioning
confidence: 99%
“…The solvothermal reaction takes place in a sealed and negative pressure environment, which is conducive to the full reversible reaction, long reaction time and sufficient crystallization time [72]. The β-ketoenamine-based COFs could be obtained with high crystallinity and relatively high porosity.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23] COFs are a class of highly crystalline porous materials with predesigned pore structure, ultralarge SSA, and outstanding mechanical and chemical stability. [24] In addition to a well-defined skeleton topology and atomic periodicity, the structural tunability of COFs can be further extended to mesoscale by various strategies, [25][26][27][28][29] making COF a competitive material to build tailor-made microscopic and mesoscopic structures. For instance, our group recently proposed a reversible polycondensation-termination (RPT) strategy to prepare COF particles consisting of textured nanoflakes with a typical thickness of ≈30 nm.…”
Section: Introductionmentioning
confidence: 99%